1991
DOI: 10.1042/cs0800047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dichloroacetate and bicarbonate on haemodynamic parameters in healthy volunteers

Abstract: 1. It has been shown that sodium bicarbonate has no effect or could even be detrimental in various forms of metabolic acidosis. Dichloroacetate, a stimulator of the pyruvate dehydrogenase complex, might offer an alternative treatment. The present study therefore examines the metabolic and haemodynamic effects of dichloroacetate and sodium bicarbonate in healthy volunteers. 2. On 2 different days, sodium dichloroacetate (50 mg/kg body weight) or sodium bicarbonate (1.5 mmol/kg body weight) was given intravenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Intramuscular pH (pH i) was estimated from the chemical shift of the Pi peak relative to the PCr peak in the 31 P spectrum, by using the relationship determined by Moon and Richards 29pH i ϭ 6.75 ϩ log ͫ ␦ Ϫ 3. 27 5.69 Ϫ ␦ ͬ…”
Section: For Calculation)mentioning
confidence: 99%
“…Intramuscular pH (pH i) was estimated from the chemical shift of the Pi peak relative to the PCr peak in the 31 P spectrum, by using the relationship determined by Moon and Richards 29pH i ϭ 6.75 ϩ log ͫ ␦ Ϫ 3. 27 5.69 Ϫ ␦ ͬ…”
Section: For Calculation)mentioning
confidence: 99%
“…The metabolic effects of dichloroacetate (DCA) 1 administration have been examined in humans at rest (1,2) and during submaximal and maximal exercise (3,4). These studies have consistently demonstrated that DCA can reduce blood lactate concentration at rest and during exercise.…”
Section: Introductionmentioning
confidence: 99%
“…В исследовании на здоровых добровольцах из-учалось влияние НДХА на некоторые гемодинами-ческие параметры [28]. …”
Section: метаболические и физиологические эффекты ндха на целостном оunclassified